O pensamento evolutivo como invariante universal em biologia estruturando o ensino de citologia em nível médio - Silva Júnior, Carlos André (2016)
The evolutionary thought, especially Darwinism and its extensions, has greater importance in Biology because it bases the understanding of all the biological events. In every level, molecular or populational, ultimately, it is the assumptions of evolution that give sense to the events in the living world. The National Curriculum Parameters agrees to that; in a way that they define “origin and evolution of life” as a structuring subject of the Biology curriculum in secondary school. They suggest that the evolutionary concepts must constitute a guiding line for discussion of all the other subjects. The textbook, which is the main source of scientific information for the students and, often for the teachers, influences on the planning and execution of the classes; it aims more at exhausting the biology content than at suggesting teaching perspectives. This work consists of preparation, execution and analysis of a pedagogic sequence for the cytology teaching on the first year of secondary school. Such construction is based on the theory of conceptual fields of Vergnaud, because it considers that the conceptualization happens through situations. By understanding that, mentally, the knowledge is not organized in topics, like in textbooks and teaching plans, a pedagogic sequence was built from nine situations for the cytology teaching in such a way that it is linked to the understanding of the evolutionary theory (Darwinism/synthetic theory). The reflections that permeated the whole discussion of the pilot study not only made evident elements of a descriptive practice – which considered the use of videos, drawings or simulators, complementary to the transfer of knowledge focused on the teacher’s speech – but also allowed the establishment of a gradual appropriation process of relational pedagogy. As a teaching proposal, the teacher who adopts it has the autonomy to make choices of what and when to use it. The heart of the study is the evolutionary thought as a universal invariant, and this perspective conducted the cytology teaching through concepts articulation. This possibility can (and must) be extended to the whole Biology.